Household air pollution and childhood bronchial asthma new onset risk in Kota Bharu Kelantan: the determinants and modelling - Ibrahim, Muhammad Naim (2024)
Background: Rapid urbanisation and industrialisation have led to increasing environmental pollution, heightening children's vulnerability to bronchial asthma (BA). Environmental factors, including rising household product consumption and poorly regulated outdoor pollution, play a key role in this trend. Despite the growing risk, locally focused studies on household-related contributors to childhood BA remain limited. Therefore, this study aims to elucidate the relationship between household air pollution and the risk of childhood BA onset in Kota Bharu, Kelantan. It includes the development, validation, and reliability analysis of the HAPBAC-Checklist, as well as identifying the determinants of childhood BA onset and modelling them. Methodology: The study was conducted through two phases, from March 2023 to April 2024. The first phase involved the development and validation of the HAPBAC-Checklist, which included four stages: 1) the development of the checklist 2) content validation 3) face validation and 4) reliability analysis (kappa agreement analysis). Then, the second phase employed a case-control study involving 194 children; 97 newly diagnosed BA cases and 97 controls, in Kota Bharu, Kelantan. Data were collected using the HAPBAC-Checklist and air quality measurements. Descriptive analysis and logistic regression identified factors linked to childhood BA new onset, which were then used to develop accurate predictive models. Results: The final validated HAPBAC-Checklist consists of five domains (sociodemographic, family history of atopy, child’s medical history, household attributes, and outdoor attributes) with 59 items. The I-CVI scores indicated good relevancy (value ranged from 0.83 to 1.00), and the S-CVI value was satisfactory (value of 0.94). The I-FVI (at least 0.83) and the S-FVI (value of 0.96) indicating the checklist was easily understood. The kappa analysis for reliability testing for five domains combined was 0.88 (95% CI: 0.81, 0.95; p<0.001). A case-control study found that case group had a higher proportion of indoor smoking, indoor pets, new wooden furniture, and other household attributes. As for outdoor, the case group had a higher proportion vehicle near their homes, use outdoor wood stoves, and live closer to pollution sources such as major roads and garbage burning. Air quality measurements indicated higher pollutant levels among households in the case group. Multiple logistic regression revealed the significant determinants were younger age (AdjOR: 0.67, 95% CI: 0.50, 0.89; p=0.007), mother with history of atopy (AdjOR: 5.18, 95% CI: 1.54, 17.38; p=0.009), and sibling with history of atopy (AdjOR: 4.88, 95% CI: 1.51, 15.78; p=0.008); Household attributes: indoor smoking (AdjOR: 5.64, 95% CI: 1.95, 16.29; p=0.001), indoor pets (AdjOR: 3.65, 95% CI: 1.21, 11.04; p=0.022), recent home painting (AdjOR: 9.25, 95% CI: 1.56, 54.91; p=0.014), poorly ventilated kitchens (AdjOR: 12.28, 95% CI: 2.80, 53.87; p=0.001), frequent frying (AdjOR: 14.15, 95% CI: 3.01, 66.48; p=0.001), wood stove use indoor (AdjOR: 17.84, 95% CI: 1.29, 247.20; p=0.032) and fragrance indoor (AdjOR: 7.54, 95% CI: 2.23, 25.51; p=0.001); Outdoor attributes: proximity to main roads (AdjOR: 0.99, 95% CI: 0.98, 0.99; p=0.001) and nearby livestock or outdoor pets (AdjOR: 5.62, 95% CI: 1.82, 17.38; p=0.003); and air quality measurement: elevated levels of indoor PM10 (AdjOR: 1.03, 95% CI: 1.02, 1.05; p<0.001) and Aspergillus spores (AdjOR: 1.08, 95% CI: 1.01, 1.16; p=0.048). The predictive model developed from these 14 determinants showed an excellent fit (ROC curve = 0.947; 95% CI: 0.92, 0.97), effectively predicting childhood BA onset. Conclusion: The HAPBAC-Checklist is a novel tool specifically tailored to address locally identified household and outdoor factors influencing BA. The widespread determinants underscore the urgent need to prevent childhood BA. This study recommends policies promoting healthier living environments, incentives for safer practices, stricter regulation of household products, and health advocacy on key risk factors.